SOCIO-THEO-ANTHROPOLOGICAL CAPITAL IN BUILDING RELATIONSHIPS BETWEEN REILIGOUS PEOPLE IN MEDOWO KEDIRI - Budi Ichwayudi; Hasan Mahfudz (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
Humans as social beings, cannot live life independently, need the participation of others in living life in society. Diverse social life requires individuals to be able to adapt in society, therefore social harmony -religion- becomes a necessity that must be carried out in the midst of a heterogeneous society. This study seeks to examine more deeply about the various modalities in building religious harmony in society, in this case the Medowo community. This study uses a qualitative approach, namely by conducting interviews, observations and direct documentation of the practice of religious social life in Medowo. The results show that the community has several capitals in building religious harmony, including anthropological or cultural capital, sociological capital and theological capital.